Epidemiological and clinical features of patients infected with influenza a (H1N1) in slovenia - Maja Sočan; Katarina Prosenc Trilar; Nataša Berginc; Tatjana Frelih (Zdravniški Vestnik, 2009)
Background Introduction of the novel virus influenza A (H1N1)v in Slovenia directed enhanced surveillance and introduction of measures to delay the progress of pandemic virus. Patients and Active case finding started in April 2009 and first case was confirmed on 19th June 2009. methods Epidemiological and clinical data of first one hundred cases with confirmed influenza A (H1N1)v infection were collected. results Majority of patients, infected with novel pandemic virus, acquired the infection abroad, most often in Greece and Spain. Only three patients obtained the infection in Slovenia. The greater part of patients was young, 80 % was younger than 30 years of age. Both sexes were equally affected. Signs and symptoms did not differ from seasonal influenza: patients were subfebrile or febrile (66 %) with cough (81 %) and headache (63 %), accompanied by soar throat (59 %) and nasal discharge (54 %). Diarrhoea affected 9 % of the patients which is uncommon for influenza virus infections. The course of influenza was uneven and no one was hospitalized. Antivirals were given to majority of cases (86) and 17 (20